Fertility outcome analysis after surgical management of tubal ectopic pregnancy: a retrospective cohort study - Li, Jingwei (BMJ Open, 2015)
OBJECTIVES: To compare the subsequent fertility and risk of recurrence of an ectopic pregnancy (EP) in women who had had an EP, according to the type of surgical treatment they received—that is, salpingectomy, salpingostomy or tubal anastomosis. METHODS: A retrospective cohort study was carried out between January 2003 and September 2011 of 618 patients admitted to hospital with tubal EP and who had received surgical treatment (salpingectomy, n=434; salpingostomy, n=112; and tube anastomosis, n=72). Main outcomes included the first intrauterine pregnancy (IUP) and recurrent EP. RESULTS: The crude IUP rates up to 24 months after surgery were 55.5% for salpingectomy, 50.9% for salpingostomy and 40.3% for tubal anastomosis treatments. In the multivariate-adjusted model, with the patients receiving salpingectomy as the reference group, HR for patients after salpingostomy and tubal anastomosis treatments for IUP were 0.912 (95% CI 0.762 to 2.017) and 0.619 (95% CI 0.328 to 0.927), respectively. The 2-year cumulative recurrent EP rates were found to be 8.1% for salpingectomy, 6.3% for salpingostomy and 16.7% for tubal anastomosis treatments. Taking the patients receiving salpingectomy as the reference group, the patients who received tubal anastomosis had a positively higher risk of recurrent EP (HR=2.280; 95% CI 1.121 to 4.636) in univariate analysis. Adjustment for other potential confounders only slightly attenuated the HR. CONCLUSIONS: The patients with an EP receiving tubal anastomosis treatments appeared to have a lower 2-year rate of IUP and a higher risk of recurrent EP after adjustment for other potential risk factors.